1993
DOI: 10.2527/1993.7171817x
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular collagen characteristics of ram, wether, and zeranol-implanted ram lambs

Abstract: Eighteen spring-born Columbia ram, wether, and zeranol-implanted ram lambs were studied to determine the influence of castration or zeranol implants on intramuscular collagen (IMC) properties and muscle shear force values. Warner-Bratzler shear force values for longissimus muscle were greatest for ram lambs, intermediate for implanted rams, and least for wethers (P < .05). Nonreducible collagen crosslink concentration was greater in IMC of rams and implanted rams (P < .05). The IMC from rams compared with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
7
1
5
Order By: Relevance
“…As variações encontradas na maciez são decorrentes de vários fatores, tais como: raça dos animais [21,23,27,30], peso ou idade ao abate [34,39], tipos de músculos [1,42], sistema de manejo [27,28,36] e condições de pré e pós-abate.…”
Section: Efeito Do Peso Ao Abate De Cordeiros Santa Inês E Bergamáciaunclassified
See 1 more Smart Citation
“…As variações encontradas na maciez são decorrentes de vários fatores, tais como: raça dos animais [21,23,27,30], peso ou idade ao abate [34,39], tipos de músculos [1,42], sistema de manejo [27,28,36] e condições de pré e pós-abate.…”
Section: Efeito Do Peso Ao Abate De Cordeiros Santa Inês E Bergamáciaunclassified
“…MAIORANO et al [27], verificaram que cordeiros castrados (1,64kg) apresentaram maior maciez, seguido por cordeiros implantados com Zeranol (2,01kg) e mostraram menor maciez os cordeiros inteiros (2,45kg). No entanto, PURCHAS [36] relatou que diferenças entre ovelhas, machos inteiros e castrados são pequenas ou inconsistentes.…”
Section: Efeito Do Peso Ao Abate De Cordeiros Santa Inês E Bergamáciaunclassified
“…A primary structural attribute of collagen, determining many of its functional qualities, is crosslinking (Reiser et al, 1992). The hydroxylysylpyridinium ( HP) crosslink is relatively abundant in intramuscular collagens and has been used to measure the progression of crosslinking across a number of species in a variety of muscles (Smith and Judge, 1991;Horgan et al, 1991;Maiorano et al, 1993;McCormick, 1994). However, the HP crosslink is absent from skin collagen (Eyre et al, 1984;Yamauchi and Mechanic, 1988), present only in trace amounts in fell (McCormick, unpublished data), and occurs in relatively low levels (compared with intramuscular collagen) in epimysium (Horgan et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Six Columbia ram lambs left intact, six castrated at approximately 100 d of age, and six intact rams implanted with 12 mg of zeranol at 100 d of age were used in this study. The lambs were fed an 80% corn diet on an ad libitum basis for 70 d before slaughter at approximately 6 mo of age and a live weight of approximately 53 kg as described by Maiorano et al (1993).…”
Section: Methodsmentioning
confidence: 99%
“…Wide differences in cross-link type and concentration occur between different tissues and muscle types (McCormick, 1994). Maiorano et al (1993) reported that sex and age differences affect the amount of collagen and cross-linking in sheep. The current study with LM steaks from cattle of the same sex and relative age indicates that breed differences in tenderness could not be attributed to variation in collagen amount or the amount of cross-linking.…”
Section: Connective Tissuementioning
confidence: 99%